Bus transport user satisfaction and service quality improvement through vehicle tracking technology - Salemi, Samin (2010)
Public transportation is a principle service in every country. Increased public transport usage can solve several problems such as reduced traffic, congestion and the global warming. Public transport improvement is an issue that helps to increase public transport usage. Previous researchers have proposed several technologies to solve user problems in public transport systems and improve these public transport systems. One major problem that exists for user public transportation is high waiting time that is spent by users. The research proposes a system that users can manage their time using the system when they want to use public transportation. The system is a web-based system that shows real time positions of public vehicles such as bus so users can schedule their time for going to nearest station thus waiting time that is spent by users for using public transportation will be reduced. The proposed system has been implemented on UTM public transportation as a case study and performance of the proposed system on the case study is validated using user satisfaction and service quality indexes. Analysis of user satisfaction and service quality of the case study before and after implementation of the proposed system shows that the system has positive impact on the user satisfaction and service quality of the case study.